THE VARIETY OF FEMALE CHARACTERS IN BUKU LATIHAN TIDUR: THE COLLECTION OF POEMS BY JOKO PINURBO - Harmia, Citra Dewi; Sulistyowati, Sulistyowati (Gramatika: Jurnal Ilmiah Kebahasaan dan Kesastraan, 2023)
The development of the world of literature and poetry today has resulted the proliferation of various poems that reflect ideological and social constructions in society. One of them is narrative-style poetry which often features characters with specific identities. One of the poets who is prolific in producing literary works in the form of narrative poetry is Joko Pinurbo who is famous for his uniqueness regarding the topic of his poetry which mostly discusses female characters. This article aims to identify the various female characters in Joko Pinurbo's poetry through a semiotic perspective. The analysis used is the Charles Morris three-dimensional framework. The research method used is descriptive method, with a qualitative approach. The data source is 12 poetry titles in Buku Latihan Tidur by Joko Pinurbo's collection of poetry. The data is analyzed by describing semiotic meanings in terms of syntax, semantics, and pragmatics. Then, those data are related to the categories of Macinos' masculine and feminine traits. The result of the study shows that there is a dominance of the depiction of feminine characters towards female characters in Joko Pinurbo's poetry which represents the traces of Joko Pinurbo's ideology and gender perspective as a writer.